2015
DOI: 10.1155/2015/843959
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Human Urotensin II Enhances Macrophage-Derived Foam Cell Formation in Transgenic Rabbits

Abstract: Circulating urotensin II (UII) is involved in the development of atherosclerosis. However, the role of autocrine UII in the development of atherosclerosis remains unclear. Here, we tested the hypothesis that autocrine UII would promote atherosclerosis. Transgenic rabbits were created as a model to study macrophage-specific expressing human UII (hUII) and used to investigate the role of autocrine UII in the development of atherosclerosis. Transgenic rabbits and their nontransgenic littermates were fed a high ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The entire aortic tree was fixed in 10% neutral buffered formalin and stained with Sudan IV (Yongsheng Chemical Co., Ji'nan, China) as previously described [21]. The area of the atherosclerotic lesion (sudanophilic area) was measured using image analysis software (WinROOF 6.5, Mitani Co. Ltd., Tokyo, Japan).…”
Section: Atherosclerotic Lesion Analysismentioning
confidence: 99%
“…The entire aortic tree was fixed in 10% neutral buffered formalin and stained with Sudan IV (Yongsheng Chemical Co., Ji'nan, China) as previously described [21]. The area of the atherosclerotic lesion (sudanophilic area) was measured using image analysis software (WinROOF 6.5, Mitani Co. Ltd., Tokyo, Japan).…”
Section: Atherosclerotic Lesion Analysismentioning
confidence: 99%
“…10 27 Proinflammatory cytokines such as interleukin (IL)-6, IL-1β, and interferon (IFN)-γ in atherosclerotic plaques, which are secreted by macrophages and lymphocytes, upregulate the expression of U-II, and the specific receptor UT which accelerates the formation of atherosclerotic plaques with autocrine/paracrine effects. 28 Moreover, U-II induces proliferation of vascular smooth muscle cells 10 and cardiomyocytes. 11 Indeed, previous studies have indicated the presence of cardiac hypertrophy 29 and altered cardiac function 30 in SGA infants.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic (Tg) mice of C57BL/6 N background were generated in our laboratory as previously reported [ 26 , 27 ]. The DNA construct used for microinjection contained mouse SFRP4 cDNA under the control of the liver-specific sequences containing partial apoE and liver-specific region of the apoE/apoCI gene locus [ 28 ], along with four copies of the chicken β globin insulator ( Figure 1(a )), to prevent position effects of transgene insulators [ 29 ].…”
Section: Methodsmentioning
confidence: 99%